2016
DOI: 10.1080/0075417x.2016.1238143
|View full text |Cite
|
Sign up to set email alerts
|

The making of an abuser

Abstract: This paper investigates how it is that a child has become an abuser, and by what means that process may be deconstructed. We know that abusers generally have a childhood history of abuse, though not necessarily sexual. Since not all children who have been traumatised repeat those patterns, and inflict abuse on others, then something must have happened for these particular children in response to their abuse. The author elaborates the view that there is no such thing, to paraphrase Winnicott, as ‘an abused chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Many studies have shown that psychological as well as physical damage follow on from trauma (De Zulueta, 1993; Herman, 1992; Stevenson, 2021b). But what we mean by trauma is something that by its nature stretches the use of language because of its essential quality for the individual who is threatened with being overwhelmed by states of mind that may include pain, fear, anxiety, feelings that overwhelm our ability to put experience into language (Woods, 2016). They may also be too much to articulate by any means other than repetition and acting out.…”
Section: The Childhood Experiences Of Gay Menmentioning
confidence: 99%
“…Many studies have shown that psychological as well as physical damage follow on from trauma (De Zulueta, 1993; Herman, 1992; Stevenson, 2021b). But what we mean by trauma is something that by its nature stretches the use of language because of its essential quality for the individual who is threatened with being overwhelmed by states of mind that may include pain, fear, anxiety, feelings that overwhelm our ability to put experience into language (Woods, 2016). They may also be too much to articulate by any means other than repetition and acting out.…”
Section: The Childhood Experiences Of Gay Menmentioning
confidence: 99%